Smart Helmet / Nur Fatihah Mohd Yatim - Mohd Yatim, Nur Fatihah (2020)
The business that we do is based on our innovation and our first product is SMART HELMET. SMART HELMET is very beneficial to every people who is used a motorbike as the main transportation to go for work, class or anywhere. It is because it can help them from being wet when rain suddenly and they do not bring a rain coat on that time. On the SMART HELMET we also prepared a raincoat that is free size with bat cutting on the hand sleeve and a light and water resistance casing bag on the top of the helmet so that the person who wear the helmet can wear the raincoat less than 5 seconds at anywhere and anytime without need to stop anywhere to wear it. Hence it also can be easily fold after use.This SMART HELMET is unique, compact and portable.Besides that, we also use Portable concept so that our customer can bring this SMART HELMET anywhere.Our target market are household and worker persons that use a motorcycle as it main transportation to go to work or any where else.This product is easily reached and receptive because we sell this product online and also wholesale through manufacturers represented. For those customer who want to get this product, they can order through our official website or get directly from our company. The competitive advantage is a set of unique features of a company and its product that are perceived by the market as significant and superior to the competition. It is the reason behind brand loyalty. There are three different types of competitive advantages that our companies use. They are cost, product or service differentiation and niche strategies. Our management team include Chief Executive Officer, Chief Financial Officer, Chief Operating Officer, Chief Marketing Officer and Administration. They have different primary duties and responsibility. Lastly, we will expect that our business will become more developed in the near future because with the new innovation of our SMART HELMET concept and also based on our vision which is to become the leading motorbike accessories supplier in the international by 2030.